New smart beta index using the Rachev ratio under a non-normal return distribution. (4th June 2021) - Yamamoto, Rei; Kawadai, Naoya
In this paper, we focus on the 'Rachev ratio' proposed by Biglova et al. (2004) and propose a new smart beta index using it. This ratio has demonstrated its effectiveness as a performance measure; however, it is difficult to consider it to be a portfolio tool, particularly due to its non-convexity. Therefore, we propose a simple weighting method to construct a portfolio, transforming it into a new smart beta index. Moreover, we compare its performance with other smart beta indices in the global stock markets. The result of our empirical analysis, corroborate our contention that the proposed smart beta index using the Rachev ratio provides higher performance than other standard smart beta indices. Hence, we conclude that this smart beta is a new effective index that can be used in global stock markets.